Hak Dan Kewajiban Suami Istri Dalam Pernikahan - Naufal Arib Maulana Hasibuan; Mardhiah Abbas; Rahmat Hidayat Hasibuan; Riski Nurdilah; Baharuddin Yusuf Ritonga; Ayu Natasya; Alfa Ridha Rambe; Rusdi Satriawan Siregar (LPPI UMN AL WASHLIYAH, 2025)
This study aims to analyze the rights and obligations of spouses in marriage according to law and social norms in Indonesia. Using a qualitative method with a case study approach, data were collected through in-depth interviews and analysis of legal documents related to marriage. The results indicate that the rights and obligations of husband and wife in Indonesia are often imbalanced, with husbands being more inclined to act as breadwinners and wives bearing more household responsibilities. Additionally, the findings reveal a gap between written law and practice in the field. The conclusion suggests that better education for married couples about their rights and obligations is needed, as well as stricter law enforcement to ensure marriage equality.